2015
DOI: 10.1194/jlr.m056069
|View full text |Cite
|
Sign up to set email alerts
|

A lipidomic screen of hyperglycemia-treated HRECs links 12/15-Lipoxygenase to microvascular dysfunction during diabetic retinopathy via NADPH oxidase

Abstract: Diabetic retinopathy (DR), the most prevalent microvascular complication of diabetes, is responsible for over 10,000 new cases of blindness every year in the United States alone ( 1 ). The risk of vision loss increases with the development of diabetic macular edema and/or retinal neovascularization (NV), the former being a direct consequence of blood-retinal barrier (BRB) dysfunction and the latter the result of widespread retinal ischemia ( 2 ).For years, signifi cant effort has been invested in elucidating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 45 publications
1
59
1
1
Order By: Relevance
“…Type 1 diabetic rat model has shown that retinal capillary cell apoptosis, which precedes the development of histopathology characteristic of diabetic retinopathy, is not observed till 5–6 months of streptozotocin-induced diabetes [30, 31]. Although high circulating glucose is the key instigator, hyperlipidemia is also considered to play an important role in the development of diabetic retinopathy [1015, 17, 18]. Triglycerides and LDL cholesterol are shown to have a direct correlation with the incidence and severity of diabetic retinopathy, and long-term supplementation with lipid-lowering therapy, fenofibrate, reduces the need for laser treatment in patients with proliferative diabetic retinopathy [12, 14, 32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 1 diabetic rat model has shown that retinal capillary cell apoptosis, which precedes the development of histopathology characteristic of diabetic retinopathy, is not observed till 5–6 months of streptozotocin-induced diabetes [30, 31]. Although high circulating glucose is the key instigator, hyperlipidemia is also considered to play an important role in the development of diabetic retinopathy [1015, 17, 18]. Triglycerides and LDL cholesterol are shown to have a direct correlation with the incidence and severity of diabetic retinopathy, and long-term supplementation with lipid-lowering therapy, fenofibrate, reduces the need for laser treatment in patients with proliferative diabetic retinopathy [12, 14, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid-sensitive Nox2 is activated in the retina during the early stages of diabetes, increasing the levels of cytosolic ROS [9, 10, 17, 18], and increased cytosolic ROS serve as a trigger to damage retinal mitochondria [9, 10, 45]. Our study using in vitro model has shown that the addition of lipotoxic insult in a glucotoxic environment exacerbates cytosolic ROS production and accelerates mitochondrial damage [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues can metabolize fatty acids to biologically active lipid mediators through the cyclooxygenase (COX), lipoxygenase (LOX) or cytochrome P450 epoxygenase (CYP) pathways. While COX, LOX, and their products have received considerable attention in the diabetic retina171819202122232425, relatively little is known about the role of retinal CYP-derived lipid mediators. CYP enzymes are endoplasmic reticulum membrane-bound monooxygenases that oxidize a variety of substrates, including polyunsaturated fatty acids.…”
mentioning
confidence: 99%
“…Various other techniques have been optimized such as fundus fluorescein angiography [110], histology and immunohistochemistry for the tight junction components zona occludens 1 (ZO-1 = tight junction protein 1 or TJP1), claudin-5 and occludin [111,112]; quantitative fluorophotometry in rat eye [113][114][115][116] and OCT thickness measurements [116,117]. Thus, most of the techniques are focused on determining the vascular complications in the hyperglycemic eyes of STZ mice and rats.…”
Section: Diabetic Modelsmentioning
confidence: 99%